Conjugated microporous polymers bearing metallophthalocyanine moieties with enhanced visible-light photocatalytic activity. (February 2018) - Li, Qiang; Wang, Heng-guo; Li, Yanhui; Li, Yanwei; Duan, Qian
Abstract: A series of metallophthalocyanine-based conjugated microporous polymers (MPc-CMPs, M = Co, Cu, Zn) were synthesized and used for the photodegradation of organic pollutants for the first time. The as-obtained MPc-CMPs were characterized by UV-vis spectroscopy, Fourier transform infrared spectra (FTIR), scanning electron microscope (SEM). Their photocatalytic activities were assessed by the photodegradation of RhB in the presence of H2 O2 under visible light irradiation. Moreover, the possible mechanism to predict this reaction pattern was proposed. As a result, the as-obtained MPc-CMPs, especially CoPc-CMP, exhibit excellent photocatalytic efficiency, recyclability and stability. These results indicate that the MPc-CMPs are potentially applicable in the environmental purification of organic pollutants in the industrial wastewater. Graphical abstract: A series of metallophthalocyanine-based conjugated microporous polymers (MPc-CMPs, M = Co, Cu, Zn) were synthesized and used for the photodegradation of organic pollutants. Highlights: An effective strategy is proposed to synthesize conjugated microporous polymers. Conjugated microporous polymers are born with metallophthalocyanine moieties. The polymers could be used as photocatalysts under visible-light irradiation. The photocatalysts exhibit excellent photocatalytic efficiency and recyclability.